The Effects of Horse Riding Simulation Training on Stroke Patients’ Balance Ability and Abdominal Muscle Thickness Changes - Baek, Il-Hun (The Society of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to assess the effects of horse riding simulation training on changes in balance ability and abdominal muscle thicknesses of stroke patients. [Subjects] Thirty stroke patients with hemiplegia were recruited, and they were randomly assigned to a control or experimental group. [Methods] The experimental group performed horse riding simulation training, whereas the control group performed trunk exercises for 8 weeks. Balance ability was measured using a BioRescue system. The thicknesses of subjects’ external oblique, internal oblique, and transversus abdominis muscles were measured by ultrasonic imaging. [Results] In the experimental group, balance ability was significantly improved after training. Similarly, the thickness of the abdominal muscles on the affected side changed after training in the experimental group, whereas the control group showed no statistically significant changes. [Conclusion] We suggest that horse riding simulation training is more effective than trunk exercises at reducing the center of pressure path length and travel speed and improving the asymmetry of the abdominal muscles of stroke patients.